Molecular Dynamics Simulation of Wax Molecular Diffusion Behavior in Waxy Crude Oil Emulsion with Water Content - Tuerxun YILINAER·; Guangjian ZHANG; Li FU; Kaifeng FAN; Weiqiang WANG (Liaoning Shiyou Huagong Daxue xuebao, 2025)
Using molecular dynamics, the lowest energy configurations of n⁃dodecane, n⁃octadecane, and n⁃nonadecane were constructed, and the interactions between oil molecules and wax molecules were studied at different water contents (mass fractions). The molecular dynamics model of crude oil emulsion system based on different mass fraction water content was constructed. The effect of water molecules dissolved in the system on the viscosity of waxy crude oil was studied. The radial distribution functions of wax molecules in different water content systems were compared. The results show that carbon number is the main factor to determine the interaction energy between crude oil molecules. With the increase of water content, the distance between molecules increases, while the interaction energy decreases. After water molecules are dissolved in the system, the distance between wax molecules and electrostatic interaction become larger, the distribution of wax molecules becomes disordered, and the flow characteristics of crude oil are improved.